Pengendalian Lingkungan: Pengaruh Edukasi Pengolahan Sampah Organik Rumah Tangga Menggunakan Metode TAKAKURA - Dewi, Rahma; Fatmadewi, Rose; Akliyah, Lely Syiddatul; Mukhsin, Dadan; Nafis’aly, Muhammad Zharfan; Raihan, Ananda Muhammad; Kurniawan, Sophi Ayni Putri (Universitas Muhammadiyah Surakarta, 2024)
The amount of food waste and leaves generated in the city of Bandung in 2021 was 1,430.04 tons per day and will continue to increase in 2024 by 1,796.51 tons per day. This condition needs to be controlled, so that it does not cause waste problems in the city of Bandung. In light of these conditions, a team of lecturers from the Urban and Regional Planning Study Program at the Universitas Islam Bandung educated the community on the processing of food and household waste, aiming to enable the community to convert organic waste into a more beneficial resource while preventing environmental pollution, including its potential reuse as fertilizer. In order to achieve the goal of educating the community, the team conducted education on organic waste processing using the Takakura method, together with 29 women of the Ta'lim Abu Bakar Assembly at RT 001 RW 012 Sekejati Village - Buahbatu District. Service activities include 7 (seven) stages, namely planning, coordination, socialization, Pre-Test, education about waste, assistance in making products and evaluation of activities (Post-Test). In the core activity, before the presentation on the understanding of waste management using the Takakura Method, PkM participants were given a questionnaire to find out their understanding of waste and its processing system. Subsequently, the presentation of material and compost making practices using the Takakura Method was carried out, and ended with an evaluation of activities (Post-Test) with the distribution of questionnaires. The results of the PkM activity include an increase in the understanding of PkM participants from 60% to 77% after education. The highest understanding of participants in the types of organic waste and 3R waste sorting was 93%. In addition, PkM participants were also very active during the activity and continued the activity of making kompok (waste processing) using the Takakura Method in their respective homes. So it is hoped that PkM activities can help the community better understand waste sorting, the importance of sorting organic waste, a cleaner environment, and the realization of sustainability.